Malondialdehyde Production by Platelets during Secondary Aggregation - Macfarlane, D. E; Gardner, Sheila; Lipson, Carol; Mills, D. C. B (Thrombosis and Haemostasis, 1977)
A method is described for increasing the sensitivity of the thiobarbiturate assay for malondialdehyde by concentrating the coloured reaction product. The basal level of malondialdehyde-like material in plasma was found to be about 0.03 μM. Platelets synthesized malondialdehyde when stimulated by collagen or thrombin and also during the second phase of aggregation induced by ADP or adrenaline.